Comparative Spatio-Temporal Dynamics of Urban Sprawl in Algerian Cities Skikda and Tébessa (1985-2024) Using GIS and Landsat Imagery - Lounis lbtissem; Leulmi Lamia; Gherzouli lazhar; Lazri Youcef (Alanya Üniversitesi, 2024)
This study analyzes urban sprawl in the Algerian cities of Skikda and Tébessa from 1985 to 2024, utilizing supervised classification of Landsat satellite imagery and GIS analysis. Skikda, a coastal city, experienced a 68% increase in built-up areas due to industrial growth and coastal geography, whereas Tébessa, an inland city, saw a 45% increase, with growth moderated by its topography and economic structure. The findings illustrate how socio-economic factors, land-use policies, and geographical characteristics influence urban expansion patterns. Skikda's rapid, scattered growth contrasts with Tébessa's controlled expansion. This study highlights the need for customized urban planning strategies that consider local contexts to manage urban sprawl effectively. By comparing the dynamics of coastal and inland cities, the research provides valuable insights for sustainable urban development in medium-sized Algerian cities, offering a framework for similar studies nationwide.